Correlations between nuclear incompressibility, liquid-gas critical point, and quarkyonic transition - Lysenko, Artemiy; Gorenstein, Mark; Moss, Tripp; Poberezhniuk, Roman; Vovchenko, Volodymyr (Physical Review C, 2025)
We systematically probe different parametrizations of the attractive nuclear force based on real gas models to construct the nuclear matter equation of state. In each of the cases, the repulsion between nucleons is treated in the framework of excluded volume, and interaction parameters are fitted to the empirical properties of the nuclear ground state. We calculate the critical temperature T_c and critical particle number density n_c, and find that they are strongly correlated. Both are also correlated with the incompressibility K_0 in the nuclear ground state. We also include a quarkyonic matter phase in the quasiparticle description and investigate the relationships among K_0, transition density to the quarkyonic phase, n_tr, and corresponding peak in the speed of sound, v_{s, max}^2. At each density, the quark fraction is found by minimizing the energy density. We find that both n_tr and v_{s, max}^2 are negatively correlated with K_0, n_c, and T_c.